Physiological adaptations and practical efficacy of different blood flow restriction resistance training modes in athletic populations - He, Chuang; Zhu, Dinghuang; Hu, Yunzhou (Frontiers in Physiology, 2025)
Blood flow restriction resistance training enhances athletic adaptations via distinct mechano-metabolic pathways. This review synthesizes evidence comparing three blood flow restriction resistance training modalities: Low-load resistance training with blood flow restriction (using 20%–30% of one-repetition maximum) prioritizes metabolic stress (lactate and hydrogen ion accumulation, cellular swelling), activating growth hormone (GH)/insulin-like growth factor 1 (IGF-1)/mechanistic target of rapamycin (mTOR) pathways to promote type I muscle fiber hypertrophy, making it suitable for joint-sparing rehabilitation scenarios. Supplemental blood flow restriction resistance training programs combine high-load tension (utilizing 75%–90% of one-repetition maximum) with additional blood flow restriction to produce an acute synergistic effect. This method enhances the recruitment of type IIa/x muscle fibers and prolongs mTOR phosphorylation. Combined blood flow restriction resistance training employs alternating cycles of high-load phases (70%–85% 1RM) and blood flow restriction phases (hypoxia-inducible factor 1-alpha (HIF-1α)-mediated angiogenesis), optimizing phosphocreatine resynthesis and neural drive to achieve specialization of type IIx muscle fibers. Periodized application requires matching modalities with training phases: combined blood flow restriction training for hypertrophy during the preparatory phase, supplemental blood flow restriction training for strength maintenance during the competitive phase, and low-load resistance training with blood flow restriction for active recovery. This mechanistic framework supports evidence-based blood flow restriction resistance training programming to maximize athletic adaptations while mitigating injury risk.